The effect of self-acupressure on quality of life, physical and cognitive function in relapsing remitting multiple sclerosis patients: A randomized controlled study - Bilek, Furkan; Bahcecioglu-Turan, Gulcan; Ozer, Zulfunaz (Elsevier Science Inc, 2023)
Objective: This study was conducted to evaluate the effectiveness of self-acupressure on quality of life, physi-cal and cognitive functions in individuals with Relapsing-Remitting Multiple Sclerosis (RRMS). Methods: In our randomized controlled study; participants in the study group were asked to perform self-acupressure on 6 points. They were asked to perform a total of 16 sessions, 2 days a week, for an average of 27 min each session in the morning and evening. No intervention was made in the control group during the study. Data were collected using Descriptive Information Form, Multiple Sclerosis Functional Composite Test (MSFC), and Multiple Sclerosis Quality of Life 54 Scale (MSQL-54).Results: Thirty-one individuals with RRMS in each group, 25 women in the study group and 21 women in the control group, were included in the study. After the self-acupressure application, a positive and significant difference was detected in all MSFC sub-parameters (9-Hole Peg Test, Timed 25-foot Walk Test, Paced Audi-tory Serial Addition Test) values of the study group compared to the control group. In addition, after self-acu-pressure application, the study group was found to have statistically significantly higher scores in both the combined physical health and composite mental health sub-parameters of MSQOL-54 compared to the con-trol group (p < 0.05).Conclusion: We found that self-acupressure was effective in improving physical function, cognitive function and quality of life in RRMS patients. Additionally, self-acupressure is a feasible, accessible and inexpensive method in the disease management of multiple sclerosis, which needs to be treated or supported continu-ously.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: Self-acupressure; Multiple sclerosis; Quality of life; Physical function; Cognitive function